Organic agriculture opens up new markets, says FAO - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Growing consumer demand offers new opportunities for countries exporting organic agricultural produce, the Agriculture Committee of the FAO observed at its meeting on 26 January 1999. Its report asserts that 'income generated from organic...